S2k guideline: Rosacea. (5th August 2022) - Clanner‐Engelshofen, Benjamin M.; Bernhard, Dominik; Dargatz, Sonja; Flaig, Michael J.; Gieler, Uwe; Kinberger, Maria; Klövekorn, Winfried; Kuna, Anne‐Charlotte; Läuchli, Severin; Lehmann, Percy; Nast, Alexander; Pleyer, Uwe; et al.
Summary: This updated and upgraded S2k guideline deals with the diagnosis and treatment of rosacea, which is a common, chronic inflammatory skin disease mostly affecting the face. Initially, rosacea is characterized by recurrent erythema, telangiectasia and flushing. Later, the inflammatory component predominates, with persistent erythema with follicular papules, papulopustules and pustules. The development of phyma, which usually occurs on the acral localizations, is the most severe manifestation. For the treatment of rosacea, the interdisciplinary guideline committee, with representatives of the German Dermatological Society (DDG), the Professional Association of German Dermatologists (BVDD), the German Opthalmological Society (DOG), the Society for Dermopharmacy (GD), the Swiss Society for Dermatology and Venereology (SGDV) and the German Rosacea Aid e. V., recommends the avoidance of trigger factors and topical applications of metronidazole, azelaic acid or ivermectin. For symptomatic treatment of persistent centrofacial erythema, the topical vasoconstrictors brimonidine or oxymetazoline can also be used. Systemic therapy is recommended for therapy‐resistant and severe forms of rosacea papulopustulosa. The drug of choice is low‐dose doxycycline. Alternatively, low‐dose isotretinoin can be recommended. Ocular rosacea should be treated with lid margin hygiene. For topical treatment, ciclosporin eye drops, azithromycin, ivermectin or metronidazole are suggested.